A short comment on the early development of Odense - Gundersen, Olav Elias; Larsen, Johan Sandvang (Danish Journal of Archaeology, 2018)
In a recent overview of the material from eighth to twelfth century Odense, Runge and Henriksen propose to move the date of the town’s foundation by a hundred years, to the early tenth century. In this brief comment we challenge their interpretation of the earliest Odense, and point to some problems with their definition of what constitutes towns and proto-towns, as well as the analysis of the material they present.